Pemanfaatan Limbah Kulit Nanas sebagai Penstabil Biosintesis ZnO untuk Pengolahan Limbah Palm Oil Mill Effluent Kelapa Sawit - Kana; Yuniar; Cindi Ramayanti (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Oil palm is one of the most common plants in the province of South Sumatra. The income of oil palm has increased every year, and also followed by an increase in the waste produced by oil palm. The waste produced is liquid waste or known by another name POME. There is no technology that is efficient enough to process this POME waste. Photocatalyst is a technology that uses light, either UV light or sunlight, which produces radial compounds that break down the oxygen in POME. The type of catalyst used in this research is ZnO from the biosynthesis of pineapple peel, the application of the catalyst to POME waste with a catalyst variation of 120 mg and 140 mg and also variations in irradiation time of 15, 30, 45, 60 and 75. The most efficient result for the degradation of POME waste is obtained at an irradiation time of 75 minutes with 140 mg catalyst weight.